Pengaruh Pembelajaran Online dan Semangat Belajar terhadap Pembentukan Disiplin Siswa - Sudana, I Ketut; Yesy Anggreni, Ni Luh Putu (JOEAI (Journal of Education and Instruction), 2021)
This study aims to determine the effect of online learning and the spirit of learning on the formation of student discipline at Engineering Vocational School in Denpasar. Data were analyzed by statistical analysis of simple linear regression and multiple linear regression. The results of the study, through prediction results with predictors X1 (Online Learning) and X2 (Spirit of Learning) to Y (Formation of Student Discipline), obtained the Freg value of 75.40. With (N-m-1) in this case db = 75/2, with a significance level of 5%, the Ftable value is 3.12. This means that the regression line analyzed is significant to be used as a basis for prediction because there is a significant relationship between the criteria (Y) and the predictors (X1, X2). Freg is greater than the F table value or 75.40 > 3.12. So the null hypothesis tested was rejected and the alternative hypothesis was accepted which showed that there was a significant relationship between online learning and learning enthusiasm on the formation of student discipline. Relative Contribution (SR%) for each predictor, namely X1 (Online Learning) = 68.60%, and X2 (Learning Spirit) = 31.40%. While the regression line is 49.73% which consists of the effective contribution of the X1 predictor (Online Learning) = 34.12%. And the effective contribution of the X2 predictor (Learning Spirit) = 15.61%. While the remaining 50.27% is influenced by other factors. In conclusion, there is a significant relationship between online learning and enthusiasm for learning on the discipline formation of the Denpasar Engineering Vocational High School students. Keywords: Online Learning, Discipline Forming, Enthusiasm